2021
DOI: 10.3389/fped.2021.748467
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Coronary Artery Aneurysms in Children With Kawasaki Disease Before Starting Initial Treatment

Abstract: Background: Precisely predicting coronary artery aneurysms (CAAs) remains a clinical challenge. We aimed to investigate whether coronary dimensions adjusted for body surface area (Z scores) on baseline echocardiography and clinical variables before primary treatment could predict the presence of late CAAs.Methods: We conducted a retrospective study including children hospitalized for Kawasaki disease and received intravenous immunoglobulin within 10 days of illness. We defined late CAAs as a maximum Z score (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Previous studies indicated that abnormal coronary and extra-coronary findings on initial echocardiography may be associated with resistance to IVIG 15 , 19 and subsequent CAA development. 20 , 24 , 22 Our study confirms, in two European KD cohorts, the association between a coronary artery maximal Z-score ≥ 2.0 at the initial echocardiography and severe KD, as measured by the need for second-line treatments and persistence of fever 48h after the end of initial IVIG treatment. Baseline z scores had moderate sensitivity and the highest specificity of all the models in this cohort.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies indicated that abnormal coronary and extra-coronary findings on initial echocardiography may be associated with resistance to IVIG 15 , 19 and subsequent CAA development. 20 , 24 , 22 Our study confirms, in two European KD cohorts, the association between a coronary artery maximal Z-score ≥ 2.0 at the initial echocardiography and severe KD, as measured by the need for second-line treatments and persistence of fever 48h after the end of initial IVIG treatment. Baseline z scores had moderate sensitivity and the highest specificity of all the models in this cohort.…”
Section: Discussionsupporting
confidence: 82%
“…However, it has also been proposed to be useful in the risk stratification of patients with KD. 15 , 19 , 20 , 21 , 22 Recent studies have proposed that abnormal findings on initial echocardiography may be associated with resistance to IVIG 15 , 19 in European populations and a baseline coronary artery maximal Z-score ≥ 2.0 in children is predictive of subsequent CAA development in Asian 22 and North American 20 populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, these differences in CAL diagnoses were based on the relevant diagnostic guidelines at that time. Because the Z score was clinically used for a short time, less than half of the articles (7/19) defined CALs by Z score ( 5 , 14 , 16 , 17 , 21 , 24 , 25 ). Four of these articles were published in the last 3 years.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies used data on patients with KD from different regions of Asia, such as China (20,27,29), Taiwan (16,22,24), Japan (13, 21, 25), Korea (14,26,30), and Thailand (18). Four studies were published in Europe, including Poland (15), Spain (19), Turkey (23) and France (28).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation